Ewolucja informacyjnych systemów wczesnego ostrzegania - Jelonek, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents the aspects of evolution of early warning systems (EWS), which a particularly visible in the spheres of quality changes in input information supplied to the management. The scope of utilization of these systems from the operational level to the tactical and strategic levels has occurred. Also, the tools of information processing, analysis and presentation in the system are undergoing changes. The directions of development of EWS as e-business applications have been considered and solutions enabling the creation of e-EWS systems have been shown. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 60-67